Computer Mediated Communication Dalam Perencanaan Pembangunan Daerah Provinsi Sulawesi Barat - Arianto Arianto; Tuti Bahfiarti; Erik Kalalembang (Avant Garde, 2020)
Computer Mediated Communication (CMC) is a form of communication activities through the use of computer media with internet networks. The use of CMC for digital development planning is to use e-planning applications as innovations from information media in the preparation of electronic-based regional development planning documents. The West Sulawesi Provincial Government as part of the provinces in Indonesia has used this information technology media. The research objective is to provide an overview of the use of e-planning website based Computer Mediated Communication (CMC) in compiling and setting regional planning priorities. The research method used refers to the type of descriptive qualitative research refers to the type of case study research. The type of data used is primary and secondary data from various sources. Data were collected using the main instruments in-depth interviews and observations to a number of research informants obtained based on purposive sampling techniques. Furthermore, the data collected has been analyzed qualitatively for inductive inference. The results of the study found that Computer Mediated Communication (CMC) in regional development planning in West Sulawesi Province uses website-based eplanning. The use of e-planning applications in the form of features is used for the input of RPJMD, Renstra, Pokir, and Musrembang documents. Furthermore, there are monitoring and control features, integrated in the determination of the budgeting program. Finally, the means to provide information for the process of finalizing the decision making is the priority of the implementation of regional development planning based on public interests.